Restoring hope peacekeeping the East Timor experience - De los Santos, Jaime S.; Burgos, Arnulfo Marcelo B. (AM Cleofe Prints, 2001)
"Restoring Hope outlines the performance of the United Nations Peacekeeping Force in East Timor. It recounts the compelling story of a successful mission in realizing the aspirations of a beleaguered nation towards freedom and independence. This book showcases the UNTAET and PKF as the scored both political and military victories. They reestablish peace and security. They anchored the stability of the country through the exercise of military options and diplomatic initiatives. They rehabilitated its damaged infrastructure, and reinvigorated the economy. By these feats, they were able to gain the goodwill of the East Timorese. Their accomplishments stand as a legacy to all freedom loving countries."--Preface.